Dealing with Difficult Faculty - Janet L. Gooch Ph.D., CCC-SLP (Academic Chairpersons Conference Proceedings, 2016)
Difficult faculty may harass colleagues, staff, or students, may avoid their teaching, research and/or service obligations, and make the work environment difficult. This interactive workshop will provide strategies for Chairs dealing with difficulty faculty. Particular case studies will be presented and problem-solved by participants.
Keywords: faculty; conflict-management; academic leadership; interaction styles